Proud lonely athletes: Using network centrality analysis to clarify the societal values of sports after the 2011 disaster in Japan - Sasaki, Koh (Advances in Social Sciences Research Journal, 2015)
This research builds on our previous study, examining recognition of social management and observes the interpretation of benevolent sports activities following Japan’s 2011 earthquake and tsunami. After the incident, most sports and recreational activities were suspended; however, various benevolent sports activities were arranged to benefit the damaged areas. This study investigates the recognised human value structure of sports in situation of great public anxiety by applying the life management concepts of time perspective and hope. Cluster analysis (Ward’s method) was conducted to further explore the relationships structure in the values complex. The results regarding the terminal values study suggest the greatest recognition of ‘hope for the future’, ‘family bonds’, ‘excellence’, ‘global concern’ and ‘life force’. Furthermore, the instrumental values study suggest greatest recognition of the ‘ambitious’, ‘courageous’, ‘self-reliant’, ‘competent’ and ‘respectful’ that indicate concern for inner motivation and survival capability. Network analysis (graph theory and centering resonance analysis) presents a holistic evaluation method for the positional functions of societal values and organization. This network centrality analysis clarifies the human values communicated by sports after the 2011 disaster. The comparison of national certified sports coaches, university students in sport science and university students in engineering reveals that athletes’ lives are difficult and they experience loneliness while achieving victories and records. They feel pressurized to be the last man on the podium. Therefore, they might desire true friendship and family bonds with people sharing the same supreme desire, like fellow soldiers. However, if the loneliness is accompanied by some sense of societal pride, the combination could offer a positive social force for the future.